"Snake Fang" Sign without Carotid Stenosis on Duplex Ultrasonography Indicates High Risk of Artery‐to‐Artery Embolic Stroke. Issue 4 (28th December 2012) - Tateishi, Yohei; Tsujino, Akira; Hamabe, Jumpei; Tasaki, Osamu; Morikawa, Minoru; Hayashi, Tomayoshi; Horie, Nobutaka; Hayashi, Kentaro; Suyama, Kazuhiko; Nagata, Izumi
ABSTRACT BACKGROUND AND PURPOSE Artery‐to‐artery embolism generally occurs in patients with not only moderate to severe arterial stenosis but also plaque vulnerability. Two unique cases with free‐floating thrombi at the distal side of the small plaque in the internal carotid artery without stenosis are presented and its clinical implications are discussed. RESULTS Two middle‐aged men suffered embolic stroke. Initial duplex ultrasonography revealed small plaques and vortex flow without significant stenosis or plaque vulnerability in their internal carotid arteries. Continuous examination by duplex ultrasonography showed that free‐floating thrombi developed and regressed at the distal side of the small plaques. Histological examination disclosed plaque erosion at the distal side of the plaques without lipid core rupture. CONCLUSIONS In these two cases, duplex ultrasonography revealed free‐floating thrombi developed at the distal region of small plaques. Aggressive treatment should be considered in a patient with thromboembolic stroke who has the small plaque presenting "snake fang" sign even if there is no stenosis or plaque vulnerability.